Attitudes, beliefs, and norms about sex and sexuality among young Indian male adults: A qualitative study - Zohourian, Tirajeh (Indian J Sex Transm Dis AIDS, 2020)
OBJECTIVE: Little is known about the risky sexual behaviors, attitudes, beliefs, and sources of information regarding sexual health among young adult Indian males. Currently, students in Indian secondary schools do not receive a structured comprehensive sexual health education. This qualitative study explored the sources of information, knowledge, and attitudes around sexual behaviors among young men in Mysore, India. MATERIALS AND METHODS: Between May and June 2011, 23 semi-structured qualitative in-depth interviews with males aged 18–25 years were conducted to explore their views on sexual norms, attitudes, and their sources of information to gain knowledge about sexual health. Interviews were audio recorded and transcribed verbatim. Thematic analyses were conducted. RESULTS: Participants shared a desire for quality sex education in schools but described their current sexual health curriculum as inadequate. Since social taboos dictated the space in which students gained awareness on sexual topics, the participants resorted to the outside information from both reliable and unreliable sources. CONCLUSIONS: These findings have important implications for laying the groundwork for culturally specific sexual health education interventions to meet the needs of a growing youth population in India.